X chromosome reactivation initiates in nascent primordial germ cells in mice. - Michihiko Sugimoto; Kuniya Abe (PLoS Genetics, 2007)
During primordial germ cell (PGC) development, epigenetic reprogramming events represented by X chromosome reactivation and erasure of genomic imprinting are known to occur. Although precise timing is not given, X reactivation is thought to take place over a short period of time just before initiation of meiosis. Here, we show that the cessation of Xist expression commences in nascent PGCs, and re-expression of some X-linked genes begins in newly formed PGCs. The X reactivation process was not complete in E14.5 PGCs, indicating that X reactivation in developing PGCs occurs over a prolonged period. These results set the reactivation timing much earlier than previously thought and suggest that X reactivation may involve slow passive steps.